Being social during the big dance: Social presence and social TV viewing for March Madness in public and private platforms. Issue 2 (3rd April 2021) - Kim, Jihyun; Yang, Hocheol; Kim, Jinyoung
ABSTRACT: In response to a recent trend in a TV viewing behavior, the current study examined the role of motives for social TV viewing in public and private communication platforms. Using an online survey, data were collected from college students in the U.S., who engaged in social TV viewing for March Madness, the NCAA men's basketball tournament. Primary findings indicate that the entertainment and communication motives for social TV viewing are stronger in the public platform than in private. Conversely, the social motive is slightly stronger in the private platform than in the public one. Further, in the public platform, the entertainment motive is found to be the strongest motive for social TV viewing; in the private platform, the communication motive is the strongest. Additionally, social presence has a mediation effect on social TV enjoyment.